Desemantization, Re-semantization and Elemental Materiality of Some Abandoned Houses. The Case of the "Albergo Diffuso" - Lo Feudo, Giorgio (E|C, 2023)
The widespread hotel is a tourist-type housing innovation which consists in the transformation of some old buildings, located in often abandoned and uninhabited villages, into hotel structures spread over several sites which are not always contiguous. In this article we will try to analyze this new housing structure with the lenses of semiotics, paying particular attention both to the symbolic conversions which, with the processes of desemantization and resemantization, determine its tourist-cultural form and purpose, both to the elementals components which, in our opinion, they match what A.J. Greimas and J. Fontanille consider the “phenomenal dimension, but also paradoxically real”, considered as “prerequisite of every object of semiotics”.